HR Analytics: Predicting and Enhancing Financial Performance through Human Resource Data - Nurbaiti, Beti (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2021)
The aim of this research is to investigate the predictive capabilities of HR Analytics in enhancing organizational financial performance. Employing a comprehensive literature review, this study examines the correlation between various HR metrics and key financial indicators, such as revenue growth and profitability. Methodologically, longitudinal analysis of HR practices and financial performance data is conducted to assess the predictive power of HR Analytics. The findings reveal significant correlations between HR metrics such as employee engagement, talent management practices, and training investments, and organizational financial outcomes. Specifically, organizations with engaged workforces and effective talent management strategies exhibit higher levels of profitability and innovation. Strategic investments in employee development, as evidenced by training investments, yield tangible benefits in terms of productivity and financial performance over time. These results underscore the importance of leveraging HR data to inform strategic decision-making processes and optimize HR strategies to align with broader business objectives. Moving forward, organizations are encouraged to adopt a holistic approach to HR management, integrating HR practices with emerging technologies and fostering cross-functional collaboration to drive sustainable growth and competitiveness.